Literature Review: Implementation of Posyandu Post-Covid-19 Pandemic Entering The New Normal - Shiva Nabilah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Posyandu is a form of community-based health effort that is managed and organized from, by, for, and with the community in implementing health development, to empower the community and provide convenience to the community in obtaining basic health services to accelerate the reduction of maternal and infant mortality. So far, the posyandu has a significant role in monitoring nutrition and children's health, since the COVID-19 pandemic the posyandu's role has been disrupted. Corona Virus Disease 2019 is a virus that was newly discovered in Wuhan, Hubei, China at the end of December 2019. This study aims to determine the description of the implementation of the posyandu after the COVID-19 pandemic entered the new normal period. The type of research literature review is a description of the theory, findings, and other research materials that are by the topic of discussion. The results of a literature review from 10 (ten) journals show that posyandu services have been carried out by paying attention to health protocols with facilities such as hand washing facilities/provision of Hand Sanitizer, body temperature measuring devices, Face Shield and PPE. The implementation of posyandu has complied with the Health Protocol following the technical instructions given by the ministry of health of the Republic of Indonesia. It is hoped that midwives, cadres, and the community in implementing the Posyandu after the COVID-19 pandemic enters the new normal period will continue to pay attention to health protocols.